Trends in Suicidal Ideation and Self‐Harm Among Privately Insured Delivering Women. (20th August 2020) - Zivin, K.; Dalton, V.; Tilea, A.; Admon, L.; Kolenic, G.; Fowler, R.; Haffajee, R.; Zochowski, M.; Muzik, M.; Ettner, S.
Abstract : Research Objective: Policy makers, clinicians, researchers, and the general public are all paying increasing attention to disturbing trends regarding growing rates of maternal mortality. Suicide deaths are a significant contributor to maternal mortality and continue to rise. In this context, we sought to identify trends in suicidal ideation and self‐harm in a large national cohort of privately insured delivering women. Study Design: The MAternal Behavioral Health PoLicy Evaluation (MAPLE: R01 MH120124) study uses administrative health plan data to develop predictors and health service utilization outcomes associated with suicidal ideation and self‐harm in this high‐risk patient population. We will present the baseline characteristics of our study population in addition to trends. Population Studied: This study includes 1 750 000 privately insured delivering women between 2005 and 2017 using data from a large national database of multiple health plans. The study sample includes women aged 15‐44 continuously enrolled in a single health insurance plan for one year before and one year after delivery. We identified suicidal ideation, self‐harm, depression, and anxiety using ICD‐9 and ICD‐10 diagnosis codes. Principal Findings: We found that rates of suicidal ideation rose from 34.8 per 100 000 women in 2005 to 318.7 per 100 000 women in 2017. Rates of intentional self‐harm rose from 34.8 per 100 000 women in 2005 to 122.2 per 100 000 women in 2017. Rates of either suicidal ideation or self‐harm rose from 69.6 per 100 000 women in 2005 to 440.9 per 100 000 women in 2017. Among women with a diagnosis of perinatal depression or anxiety, rates of either suicidal ideation or self‐harm rose from 123.9 per 100 000 women in 2005 to 909.1 per 100 000 women in 2017. Among women without a diagnosis of perinatal depression or anxiety disorder (PMAD), rates of either suicidal ideation or self‐harm rose from 58.2 per 100 000 women in 2005 to 307.9 per 100 000 women in 2017. Stated another way, suicidal ideation rose over eightfold during the observation period, self‐harm increased 2.5 times, and ideation or self‐harm increased over fivefold. Among women with PMAD, ideation or self‐harm among women increased 6.3 times compared to those without PMAD, for whom ideation and self‐harm increased 4.3 times. Conclusions: Rates of suicidal ideation and self‐harm increased substantially over a thirteen‐year period. Even accounting for potential coding changes associated with conversion from diagnosis using ICD‐9 to ICD‐10, changes in access to mental health care due to mental health parity and the Affordable Care Act during the observation period, these increases remain alarming. Given that publicly insured women typically face higher rates of morbidity and mortality than do those who are privately insured, these statistics likely underrepresent the burden of severe mental distress among all perinatal women. Implications for Policy or Practice: Policy makers, health plans, and clinicians should ensure access to screening and appropriate treatment for high‐risk delivering and postpartum women and to seek additional health system and policy avenues to mitigating this growing public health crisis. Primary Funding Source: National Institutes of Health.